2012
DOI: 10.1093/ntr/nts175
|View full text |Cite
|
Sign up to set email alerts
|

Research Required for the Effective Implementation of the Framework Convention on Tobacco Control, Articles 9 and 10

Abstract: This paper is part of a series of articles intended to set out the research questions that are relevant to the successful implementation of the various provisions of the Framework Convention on Tobacco Control (FCTC). This paper focuses on issues affecting Articles 9 and 10 of the FCTC. This paper focuses on the research that is most important for most countries, rather than on what is desirable in countries with high levels of research capacity.Articles 9 and 10 of the FCTC address the regulation of contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In addition, the tobacco industry has continued efforts to downplay the potential harms of cigarette smoke chemicals and to resist providing reliable chemical information, thereby undermining enactment of disclosures. 25,26 Perhaps as a consequence of the general lack of awareness of cigarette smoke chemicals, we found that fewer than half of both adolescents and adults correctly attributed the source of most chemicals to the tobacco combustion process, pointing to the need for increased efforts to promote accurate understanding of the source of greatest harm from chemicals in cigarette smoke. It is also troubling that accurate perceptions of chemical source actually decreased for both adults and adolescents.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the tobacco industry has continued efforts to downplay the potential harms of cigarette smoke chemicals and to resist providing reliable chemical information, thereby undermining enactment of disclosures. 25,26 Perhaps as a consequence of the general lack of awareness of cigarette smoke chemicals, we found that fewer than half of both adolescents and adults correctly attributed the source of most chemicals to the tobacco combustion process, pointing to the need for increased efforts to promote accurate understanding of the source of greatest harm from chemicals in cigarette smoke. It is also troubling that accurate perceptions of chemical source actually decreased for both adults and adolescents.…”
Section: Discussionmentioning
confidence: 91%
“…Similar findings have been reported in other studies. [ 19 , 20 ] Finally, the major perceived needs for public disclosure were “consumer right to know” among smokers and “smoking prevention” among nonsmokers. Thus, detailed disclosure of tobacco and smoke components would aid quitting by smokers and encourage nonsmokers to continue to abstain, which are the desired outcomes of Articles 9 and 10.…”
Section: Discussionmentioning
confidence: 99%
“…Given the huge variation in the toxic contents of currently available SLT products, it becomes extremely imperative to consider the acceptable levels of harm. According to Gray and Borland 70 , there are three major regulatory possibilities for tobacco: ( i ) regulation of carcinogens and toxins such as TNSAs, B[a]P and metals; ( ii ) regulation of nicotine for addictiveness, and ( iii ) regulation of additives. Considering the wide variations in chemical content and lack of monitoring agencies, there is an immediate need to develop validated methods for estimating the toxicity/carcinogenicity of SLT products 70 .…”
Section: Regulation Of Tobacco Productsmentioning
confidence: 99%